2009
DOI: 10.5014/ajot.63.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Parent Reports of Sensory Experiences of Preschool Children With and Without Autism: A Qualitative Study

Abstract: This study describes children’s “sensory experiences”, generates parents’ perceptions and explanations of these experiences, and compares these experiences across children with and without autism. Parents of 66 preschoolers (29 typically-developing; 37 with autism) were interviewed using a Critical Incident Technique. Parents described a situation where their child had a “good” sensory experience, a situation where their child had a “bad” sensory experience, and their own perception of how these situations fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 22 publications
7
83
0
1
Order By: Relevance
“…The participants were all in agreement that control was extremely important, and it was a theme which was discussed openly within the group: "one of the themes I've noticed come up a lot is control … if they've got control over the sensory stimulus then it's much less distressing". Dickie et al (2009) also found that uncontrollable stimuli were more distressing for both children with ASD and controls than sensory stimuli that could be induced and terminated by the children themselves, while Ashburner et al…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The participants were all in agreement that control was extremely important, and it was a theme which was discussed openly within the group: "one of the themes I've noticed come up a lot is control … if they've got control over the sensory stimulus then it's much less distressing". Dickie et al (2009) also found that uncontrollable stimuli were more distressing for both children with ASD and controls than sensory stimuli that could be induced and terminated by the children themselves, while Ashburner et al…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, although other studies report similar themes of control and avoidance (Dickie et al, 2009;Ashburner, Bennett, Rodger, & Ziviani, 2013) and uncomfortable physical responses (Kirby et al, 2014), both of these studies recruited a sample of children, rather than adults. There is some evidence that sensory reactivity may change as we age (Kern et al, 2007), therefore it is important to ascertain that these aspects of sensory experience are important to adults with ASD as well as children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations